IMPROVING FINE MOTOR ABILITIES THROUGH FINGER PAINTING ACTIVITIES AT THE AGE OF 5-6 YEARS AT PAUD CEMPAKA PETUKANGAN SELATAN - Qotrun Nada; Izfanna, Duna; Pipit Nuri Mulyaningtias (Universitas Darunnajah, 2025)
At PAUD Cempaka Petukangan Selatan, the fine motor skills of children aged 5 to 6 years are still relatively low, one of the reasons is that children cannot look good when doing activities such as drawing and folding. This is the main reason researchers improve fine motor skills. One way is to use finger painting activities. Painting with fingers is one way to improve children's fine motor skills. Because choosing the right method can help educators succeed. This research aims to determine the success of implementing finger painting activities to improve fine motor skills through finger painting activities and to find out whether it is possible to develop fine motor skills in children aged 5-6 years at PAUD Cempaka Petukangan Selatan. This type of research is called classroom activity research, which focuses on classroom situations, or what is usually called classroom action research. Data collection tools consist of observation, interviews and documentation. Analyze classroom action survey data in a series of multicycle steps. This cycle consists of four stages: planning, taking action, observing, and reflecting